Céad Míle Fáilte – How the Land of a Thousand Welcomes Coped with Mass Immigration - Fávero, Daniela Nicoletti (ABEI Journal, 2021)
The Irish short story, highlighted in the national literary production and celebrated for reflecting the social upheavals that Ireland has gone through, is nowadays configured as the genre to echo an environment in metamorphosis. This article, derived from my doctoral research, highlights the relationship between the short story and the representation of identities involved in immigration. In it, I offer an analytical reading of two short stories, “The Summer of birds”, by Gerard Donovan, and “Fjords of Killary”, by Kevin Barry, selected for their portrayal of the clash between natives and immigrants, vertically analysing the literary pieces seeking to show how Ireland is revealed in literary textuality. It is proposed that immigrants were somewhat relegated to the margins, suffering the consequences of social inequality accentuated by the Celtic Tiger period, bringing the issue of Irish identity to the centre of the discussion.